ISLAMISASI ILMU PENGETAHUAN AL-ATTAS MENJAWAB PROBLEMATIKA SEKULARISME TERHADAP ILMU PENGETAHUAN - Amir Sahidin (IMTIYAZ: Jurnal Ilmu Keislaman, 2022)
Secularism is a thought born of Western perspectives and experiences, which has had a negative impact on contemporary science. The bad impact is based on the conception of secularism itself, in the form of disenchantment of nature, or the emptying of the universe from religious and spiritual values; desacralization of politics or political exclusion from religious and spiritual elements; also deconsecration of false or relativizing human values, so that there are no absolutes in a truth. For this reason, Syed Naquib al-Attas sees the need for the Islamization of knowledge to answer the problem of secularism. Through a library research type study with a descriptive-analytical approach, it can be concluded that al-Attas' Islamization of knowledge answers the problem of secularism in science with three things. First, it frees people from the ideology and perspective of secularism. Second, dewesternization or separating important concepts and elements that make up Western civilization and culture. Third, integration or incorporating important concepts and elements of Islam into science that has been sterilized from important Western concepts and elements. These three things are an attempt to answer the problems of secularism in science.